The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1017/s0954579413000357
|View full text |Cite
|
Sign up to set email alerts
|

Interaction matters: Quantifying Conduct Problem × Depressive Symptoms interaction and its association with adolescent alcohol, cigarette, and marijuana use in a national sample

Abstract: Substance use is a major contributor to morbidity and mortality among American adolescents. Conduct problems and depressive symptoms have each been associated with adolescent substance use. Although they are highly comorbid, the relation of the interaction of conduct problems and depressive symptoms to substance use in not clear. In a national sample of 8th, 10th, and 12th grade students from Monitoring the Future surveys, latent moderated structural equation modeling was used to estimate the association of co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
37
1
4

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(47 citation statements)
references
References 69 publications
5
37
1
4
Order By: Relevance
“…Adolescents with comorbid depressive and conduct symptoms did not endorse unique items in comparison with early adolescents who endorsed only depressive or conduct symptoms; however, they did endorse a greater number and severity of symptoms (Mezulis et al, 2006). Substance use is considered nonnormative behavior during the middle school years (Maslowsky & Schulenberg, 2013). For adolescents with comorbid depressive and conduct symptoms, the use of substances may simply reflect the greater severity of distress or poorer general emotional health status.…”
Section: Discussionmentioning
confidence: 99%
“…Adolescents with comorbid depressive and conduct symptoms did not endorse unique items in comparison with early adolescents who endorsed only depressive or conduct symptoms; however, they did endorse a greater number and severity of symptoms (Mezulis et al, 2006). Substance use is considered nonnormative behavior during the middle school years (Maslowsky & Schulenberg, 2013). For adolescents with comorbid depressive and conduct symptoms, the use of substances may simply reflect the greater severity of distress or poorer general emotional health status.…”
Section: Discussionmentioning
confidence: 99%
“…Although Conduct Problems (CPs) and other externalizing problems are well-established risk factors for adolescent substance use (King et al, 2004; Maslowsky et al, 2013), the role of internalizing symptomatology (IntSx) in teen substance use risk is less clear. Some research shows that anxiety and depression are associated with subsequent substance use in adolescents (Buckner et al, 2008; Crum et al, 2008; King et al, 2004; Sartor et al, 2007); however, results are not always replicated (Pardini et al, 2007) and do not appear to be as strong as the corresponding risk of substance use associated with CPs (King et al, 2004; Maslowsky and Schulenberg, 2013). Further complicating matters, there is considerable comorbidity between CPs and IntSx in teens (Lewinsohn et al, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…To date, evidence indicates that both forms of psychopathology are associated with substance use independent of one another (Connor et al, 2004; Crum et al, 2008; Ingoldsby et al, 2006; King et al, 2004), incrementally to one another (Brook et al, 2015; Ingoldsby et al, 2006; Lansford et al, 2008), and interactively (e.g., Marmorstein and Iacono, 2001; Maslowsky and Schulenberg, 2013). These latter studies of adolescents have found that high levels of both CPs and depressive symptoms are associated with a disproportionately larger increase in risk for substance use than either disorder independently (i.e., synergistic interaction; Marmorstein and Iacono, 2001; Maslowsky and Schulenberg, 2013; Miller-Johnson et al, 1998; Pardini et al, 2007). However, research has yet to examine whether this interactive relationship exists between CPs and other forms of IntSx, such as the various type of anxiety disorder symptoms often present in adolescents (Grant et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…stealing, lying, skipping school, fighting) reflect a range of externalizing behaviors that are strongly associated with adolescent substance use (Brown et al 1996; Connor, Steingard, Cunningham, Anderson, & Melloni, 2004; Couwenbergh et al, 2006; King, Iacono, & McGue, 2004; Maslowsky & Schulenberg, 2013). In addition to more severe behaviors seen only in Conduct Disorder (e.g.…”
Section: Introductionmentioning
confidence: 99%